Long term effects of fire on ectomycorrhizas and soil properties in Nothofagus pumilio forests in Argentina - Longo, Maria Silvana (2011)
The forests of Nothofagus pumilio have historically been affected by forest fires. The effects of fire on certain above and belowground, biotic and abiotic components of these ecosystems have been previously documented, albeit belowground components have received much less attention. It has been suggested that the effects observed in the short-term after a fire usually differ from the longer-term effects. The long-term effects of fire (i.e. >5 years after burning) on belowground components in Nothofagus forests are currently unknown. In the present study we evaluated the long-term effect of fire on ectomycorrhiza (ECM) colonization and morphotype composition in N. pumilio roots, as well as soil chemical properties in temperate forests in Patagonia. Sampling was conducted in three mature monospecific forests. In each, nearby burned and unburned sites were selected. The time since the occurrence of fires differed between areas (i.e. 6?10 years). Within each site, 3 transects of 40 m were established randomly along which 5 samples of roots and soil were collected in spring and autumn. The main results were: (1) in comparison with the unburned site, ECM colonization was lower in the burned site in the area with the shorter time length since fire occurrence and no effects in the other two areas were observed; (2) richness and diversity were not significantly affected by fire but there was a significant effect of season for both parameters, being higher in spring; (3) ECM dominance was significantly higher in the unburned than in the burned site in Tronador, while in Challhuaco the opposite was observed, mainly in autumn; (4) in general carbon, nitrogen and phosphorous decreased while pH increased in the burned sites; (5) ECM colonization positively correlated with NH4+ and phosphorus and negatively with pH but was not significantly correlated with organic matter or any other soil variable. Altogether the results suggest that effects of fire on ectomycorrhiza and soil properties in N. pumilio forests are probably related to the time elapsed since fire occurrence combined with site characteristics. In addition, the direct and indirect effects of fire in these forest systems may persist for more than 10 years.